Rangeland resource assessment across the African continent for improved ecosystem health and sustainable food systems - GMV Innovating Solutions; International Livestock Research Institute (International Livestock Research Institute, 2022)
This assessment was commissioned by UNEP Kenya and contributes to the UN resolution 2/24 on combating desertification, land degradation and drought and promoting sustainable pastoralism and rangelands; and UN resolution 4/15 on innovations in sustainable rangelands and pastoralism, as well as the UNEP-led gap analysis on rangelands and the resulting report: Rangelands: A case of benign neglect and is a valuable input to the UN Decade for Ecosystem Restoration. This rangeland resource assessment also compliments the global Rangelands Atlas produced in 2021 as a collaboration between UNEP, ILRI and other stakeholders; contribute to a baseline for the development of a GEF-funded global project on rangeland restoration and the development of a rangeland monitoring system for Africa led by the European Space Agency and a global rangelands data platform led by ILRI. This research also contributes to the Livestock and Climate initiative and the Climate Security initiative of the One CGIAR. GMV and ILRI thank all funders who supported this research. More broadly the assessment contributes to discussions and interventions focusing on One Health, with rangelands health being an important pillar of this, as well as sustainable food systems. This includes attention to such as land degradation, climate impacts on livestock and other environmental challenges, and allows better analyzing opportunities for more sustainable investments in rangelands through restoration or other livestock production systems.